Emerging contaminants and antibiotic resistance in the different environmental matrices of Latin America. (December 2019) - Reichert, Gabriela; Hilgert, Stephan; Fuchs, Stephan; Azevedo, Júlio César Rodrigues
Abstract: This review aims to gather and summarize information about the occurrence of emerging contaminants and antibiotic resistance genes in environmental matrices in Latin America. We aim to contribute to future research by compiling a list of priority pollutants adjusted to the needs and characteristics of Latin America, according to the data presented in this study. In order to perform a comprehensive research and secure a representative and unbiased amount of quality data concerning emerging contaminants in Latin America, the research was performed within the Scopus® database in a time frame from 2000 to July 2019. The countries with higher numbers of published articles were Brazil and México, while most studies were performed in the surroundings of Mexico City and in Southern and Southeastern Brazil. The main investigated environmental matrices were drinking water and surface water. The presence of antibiotic resistance was frequently reported, mainly in Brazil. Monitoring efforts should be performed in other countries in Latin America, as well as in other regions of Brazil and México. The suggested priority list for monitoring of emerging contaminants in Latin America covers: di(2-ethylhexyl) phthalate (DEHP), bisphenol-A (BP-A), 4-nonylphenol (4-NP), triclosan (TCS), estrone (E1), estradiol (E2), ethinylestradiol (EE2), tetracycline (TC), amoxicillin (AMOX), norfloxacin (NOR), ampicillin (AMP) and imipenem (IMP). We hope this list serves as a basis for the orientation of the future research and monitoring projects to better understand the distribution and concentration of the listed emerging substances. Graphical abstract: Image 1 Highlights: There is a lack of information in most countries in Latin America. Brazil and Mexico published most of the papers. More research is necessary in soils, groundwater and coastal areas. Further investigations about antibiotic resistance in the area should be performed. The priority list cover plasticizers, phenols, antimicrobials and pharmaceuticals. Abstract : This paper is an overview of the published data of emerging contaminants and antibiotic resistance in Latin America, showing research gaps and suggesting a priority list for future regulation.